Imaging the evolution of lithium-solid electrolyte interface using operando scanning electron microscopy - Lihong Zhao; Min Feng; Chaoshan Wu; Liqun Guo; Zhaoyang Chen; Samprash Risal; Qing Ai; Jun Lou; Zheng Fan; Yue Qi; Yan Yao (Nature Communications)
Abstract The quality of Li–solid electrolyte interface is crucial for the performance of solid-state lithium metal batteries, particularly at low stack pressure, but its dynamics during cell operation remain poorly understood due to a lack of reliable operando characterization techniques. Here, we report the evolution of Li–electrolyte interface with high spatial resolution using operando scanning electron microscopy under realistic operating conditions. By tracking the stripping process of both Li and Li-rich Li-Mg alloy anodes, we show that multiple voids coalesce into a single gap and eventually delaminate the interface in Li, whereas the voids split and collapse to partially recover interfacial contact in Li-Mg. Density functional theory calculations show that the stronger Mg-S interaction at the metal–electrolyte interface attracts Mg toward the interface and repels Li-vacancies into the bulk, resulting in a reduced number of voids. The pressure-dependent voltage profiles of Li and Li-Mg stripping suggest that loss of contact due to void formation, rather than Mg accumulation at the interface, is the origin of high overpotential that limits the utilization of metal anodes. Improved interfacial contact enables stable cycling of all-solid-state lithium full cell at low stack pressure (1 MPa) and moderate rate (2 mA cm−2) simultaneously. The real-time visualization of Li–electrolyte interface dynamics provides critical insights into the rational design of solid-state battery interfaces.